Effect of ultrasonication on anaerobic degradability of solid waste digestate. (February 2016) - Boni, M.R.; D'Amato, E.; Polettini, A.; Pomi, R.; Rossi, A.
Highlights: The effect of sonication on digestibility of lignocellulosic residues was studied. Sonication was applied as a post-treatment of food waste digestate. Sonication positively affected the residual methanogenic potential of the digestate. The maximum biogas production exceeded that of the unsonicated substrate by 30%. Abstract: This paper evaluates the effect of ultrasonication on anaerobic biodegradability of lignocellulosic residues. While ultrasonication has been commonly applied as a pre-treatment of the feed substrate, in the present study a non-conventional process configuration based on recirculation of sonicated digestate to the biological reactor was evaluated at the lab-scale. Sonication tests were carried out at different applied energies ranging between 500 and 50, 000 kJ/kg TS. Batch anaerobic digestion tests were performed on samples prepared by mixing sonicated and untreated substrate at two different ratios (25:75 and 75:25 w/w). The results showed that when applied as a post-treatment of digestate, ultrasonication can positively affect the yield of anaerobic digestion, mainly due to the dissolution effect of complex organic molecules that have not been hydrolyzed by biological degradation. A good correlation was found between the CH4 production yield and the amount of soluble organic matter at the start of digestion tests. The maximum gain in biogas production was 30% compared to that attained with the unsonicated substrate, which was tentatively related to the type and concentration of the metabolic products.